1998
DOI: 10.1029/97jd03473
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical alkene formation in seawater from dissolved organic carbon: Results from laboratory experiments

Abstract: Abstract. The production mechanism of light alkenes, alkanes, and isoprene was investigated in laboratory experiments by measuring their concentrations in natural seawater as a function of spectral range, exposure time and origin, and concentration of dissolved organic carbon (DOC). The production mechanism of alkanes and of isoprene could not be clarified. Ethene and propene are produced photochemically from DOC. The relevant spectral range is UV and short-wavelength visible light. Initial production rates (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 36 publications
4
55
0
Order By: Relevance
“…Diurnal trends in the acetaldehyde and alkene concentrations (ethene is plotted in Fig. 9 as an example) are observed for almost the entire measurement period but are particularly evident in air with an 8 day back trajectory over the Atlantic Ocean, in-line with suggestions of oceanic sources for these species (Ratte et al, 1998;Riemer et al, 2000;Zhou and Mopper, 1993). Similar diurnal behaviour has been observed in alkene measurements made at Mace Head on the west coast of Ireland (Lewis et al, 1999) and in the Indian Ocean (Bonsang et al, 2008) but very little literature is available of measurements of acetaldehyde in the marine boundary layer environment.…”
Section: Measurements At Cvaomentioning
confidence: 70%
“…Diurnal trends in the acetaldehyde and alkene concentrations (ethene is plotted in Fig. 9 as an example) are observed for almost the entire measurement period but are particularly evident in air with an 8 day back trajectory over the Atlantic Ocean, in-line with suggestions of oceanic sources for these species (Ratte et al, 1998;Riemer et al, 2000;Zhou and Mopper, 1993). Similar diurnal behaviour has been observed in alkene measurements made at Mace Head on the west coast of Ireland (Lewis et al, 1999) and in the Indian Ocean (Bonsang et al, 2008) but very little literature is available of measurements of acetaldehyde in the marine boundary layer environment.…”
Section: Measurements At Cvaomentioning
confidence: 70%
“…Studies into hydrocarbon emissions from marine sources have demonstrated that both propene and ethene are present in natural seawater at concentrations equal to or higher than isoprene (Riemer et al 2000), but that they are produced by abiotic photochemistry acting on dissolved organic carbon (Ratte et al 1998;Riemer et al 2000). Although some macroalgal production has been shown (Broadgate et al 2004;Plettner et al 2005), phytoplankton studies have demonstrated a lack of biogenic production (Mckay et al 1996;Shaw et al 2003).…”
Section: Assessmentmentioning
confidence: 99%
“…Dashed vertical line illustrates the start of baseline production in the sample run. Data shown at a resolution of 20 s. (Ratte et al 1998). As UV wavelengths are excluded from experiments when using borosilicate glass sample vessels, the photochemical production of alkenes can be easily eliminated.…”
Section: Assessmentmentioning
confidence: 99%
“…Isoprene is produced by both phytoplankton (Broadgate et al, 1997;Ratte et al, 1998;Shaw et al, 2003) and seaweed (Broadgate et al, 2004) in the marine environment. A total global oceanic emission of 0.1-1.2 Tg C/yr has been estimated from in-situ observations (Bonsang et al, 1992;Milne et al, 1995;Broadgate et al, 1997) and satellite observations of ocean biological productivity (Palmer and Shaw, 2005), which is small compared with an estimated global terrestrial isoprene source of ∼400-750 Tg C/yr (Müller et al, 2008;Guenther et al, 2006).…”
Section: Emission Of Isoprene From the Oceansmentioning
confidence: 99%